Virtual Traces and Techno-Control of Migrants in Europe - Giacomo Buoncompagni (Journal of Sociological Research, 2024)
The development of increasingly advanced surveillance techniques and the strategic use of artificial intelligence are now intimately linked to the control of migration flows and are often a major cause of discrimination and violation of human rights and dignity. Yet such violations continue to occur amidst considerable economic investment and little oversight, in a legislative vacuum, and almost always with very little understanding of the technologies and the impact they have on the people and communities affected at the border. The article investigates all these aspects, which are still unclear, and little discussed in the institutional world and the public sphere in general. The methodology is linked to in-depth study and critical analysis of current literature on the presented topic. Comparisons between different realities and open questions will be made in order to understand the social and political gaps that are difficult to identify in this historical period. It is essential to reflect on the ethical and social issues related to the digital tracking of migration flows. The failure of institutions to act and the lack of attention of scholars and authorities would increase the risks migrants run on their journey. Migrants often lose control over their movements and choices and suffer the consequences of the decisions of systems that are considered innovative but which in the long term prove to be opaque and inefficient.